Simulation of ultra-fast dynamics effects in resonant inelastic x-ray scattering of gas-phase water - Fouda, Adam E.A.; Purnell, Gregory I.; Besley, Nicholas A. (American Chemical Society, 2018)
Resonant inelastic soft X-ray scattering maps for the water molecule are simulated by combining quantum chemical calculations of X-ray spectroscopy with ab initio molecular dynamics. The resonant inelastic scattering intensity is computed using the Kramers–Heisenberg formalism, which accounts for channel interference and polarization anisotropy. Algebraic diagrammatic construction and density functional theory-based approaches for the calculation of the X-ray transition energies and transition dipole moments of the absorption and emission processes are explored. Conformational sampling of both ground and core-excited intermediate states allows the effects of ultrafast dynamics on the computed maps to be studied. Overall, it is shown how resonant inelastic scattering maps can be simulated with a computationally efficient protocol that can be extended to investigate larger systems.